Synthesis and potentiometric analysis of organophosphorus metal complexones and complexonates based on 2-aminothiazole derivatives - Sal’keeva, L. K.; Shibaeva, A. K.; Taishibekova, E. K.; Nurmaganbetova, M. T.; Minaeva, E. V.; Sal’keeva, A. K. (SP MAIK Nauka/Interperiodica, 2011)
Synthesis conditions of 4-phenyl-2-amidothiazolyl acetate and 2-thiourido-4-diethylphosphothiazole were developed, and the complexation capacity of these compounds in formation of mixed-ligand complexes was studied. The optimal conditions and thermodynamic parameters of the complexation process were determined. The potentiometric method was used to find thermodynamic parameters of the reactions of mixed-ligand complexation with copper(II) and lead(II) ions, the composition of the complexes being formed on the basis of 4-phenyl-2-aminothiazole and its phosphorylated derivatives was determined.